2014
DOI: 10.1037/per0000027
|View full text |Cite
|
Sign up to set email alerts
|

The influence of borderline personality features on inpatient adolescent suicide risk.

Abstract: Suicide is a leading cause of death among adolescents and suicidal behavior is one of the primary risk factors for youth psychiatric hospitalizations. A number of studies indicate that depression and substance abuse are associated with suicide risk in this population, but less is known about the role of borderline personality features or their incremental influence over other known risk factors in indicating suicidal behavior among adolescents. This study examined whether borderline features were associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 60 publications
(70 reference statements)
2
12
0
Order By: Relevance
“…Consistent with the literature on PD in adults (125)(126)(127), the presence of PD in adolescents is concurrently and prospectively associated with an elevated risk for suicidal ideation and suicide attempts in early adulthood (128)(129)(130). Psychological autopsy studies of completed suicides among adolescents support these findings.…”
Section: Adverse Outcomes and Adaptive Functioningsupporting
confidence: 77%
“…Consistent with the literature on PD in adults (125)(126)(127), the presence of PD in adolescents is concurrently and prospectively associated with an elevated risk for suicidal ideation and suicide attempts in early adulthood (128)(129)(130). Psychological autopsy studies of completed suicides among adolescents support these findings.…”
Section: Adverse Outcomes and Adaptive Functioningsupporting
confidence: 77%
“…The variants of PDs associated with suicidality certainly deserve more painstaking and systematic exploration. In most of the studies considered in this review, the researchers directly addressed the role of BPD [36][37][38][39][40][41][42][43][44][45][46][47][48][49][50], probably due the importance that this PD has assumed for adult suicidal patients. Nevertheless, despite its marked incidence in these studies, BPD also showed a wide range of prevalence, with frequencies varying between 56.3 and 90.9% when considering suicidality in terms of both ideation and behaviours [34][35][36] and between 48.6 and 62% when accounting only for suicide attempts in samples with more than 100 subjects [39,44].…”
Section: Discussionmentioning
confidence: 99%
“…Although these studies included only hospitalized patients, it is interesting to compare them with the actual incidence of suicide attempts in the adolescent population: up to 10.6% for girls and 5.4% for boys and up to 3.6% for girls and 1.8% for boys for suicide attempts that required medical attention [61]. The relevance of BPD for suicidality in adolescence has also been stressed by cross-sectional studies showing that BPD mediates the impact of mood disorders on suicidal ideation and conduct [46,47] and by studies indicating how specific BPD features can incrementally influence suicidality, adding to the effect of depression and substance abuse, two prominent risk factors for adult suicidality [35,45,[48][49][50][51]. Finally, the relationship between BPD diagnosis and suicidality in adolescents also seemed to be confirmed at a longitudinal level, particularly for suicidal behaviours, but not ideation, where the presence of BPD or traits known to be predictors of suicide recurrence.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of specific personality disorders may in fact represent an activating factor [ 6 , 7 , 8 ] for stressful events [ 9 , 10 , 11 , 12 , 13 , 14 ], as well as a facilitating factor for the passage from the volitional phase to the motivational one [ 15 , 16 ]. Both in adulthood and adolescence [ 17 ], Cluster B personality disorders are the most significant predictors of suicide [ 8 ] with a prominent role being assigned to the borderline personality disorder (BPD) and its clinical traits [ 18 , 19 , 20 , 21 , 22 , 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%